Mothering and Professing in the Ivory Tower: Supporting Graduate Student Mothers - Eversole, Barbara A.W.; Crowder, Cindy L.; Lekchiri, Siham; Clark, Amber; Zimmerman, Toni S. (Journal of the Motherhood Initiative for Research and Community Involvement, 2016)
Women interested in becoming professors and mothers are often unsure of the besttime to start their families. Many women decide to become mothers in graduateschool. This article discusses the landscape for graduate students who decide to becomemothers ( gsm s) while still in school. There are several obstacles for gsm s who wishto become tenured faculty members. Institutional obstacles include the notion of idealworkers and ideal careers, which do not include the option of motherhood and oftenconflict with the notion of the ideal mother. Another obstacle is institutional genderbiases and assumptions about women, such as the bias against caregiving. Womenof any age are assumed to be responsible for caregiving of children and/or elders.Finally, women lack their own individual agency and do not have family supportto be able to be successful. gsm s can employ various strategies to overcome theseobstacles. Strategies can include institutional change strategies, department support,individual agency, and family support. Obstacles and strategies are illustrated throughpersonal vignettes from the authors’ own experiences: three authors are tenured withchildren, and two have infants and are gsm s. Two authors are or have been chairsof dissertation committees. Recommendations for institutions are offered that cansupport gsm s in their efforts to be successful at mothering and professing in theivory tower. The presented arguments make it clear that the mothering viewpointis sorely needed in the academy, and that gsm s need support from all stakeholdersin order to be successful.